2000
DOI: 10.1007/pl00008345
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of delayed cord clamping in very low birth weight preterm infants

Abstract: Delayed cord clamping of 45 s is feasible and safe in preterm infants below 33 weeks of gestation. It is possible to perform the procedure at caesarean section deliveries and it should be performed whenever possible. It reduces the need for packed red cell transfusions during the first 6 weeks of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 0 publications
5
113
1
2
Order By: Relevance
“…33 Rabe and colleagues found that preterm infants born at fewer than 33 completed weeks of gestation and who were randomized to delayed cord clamping for 45 seconds had significantly higher hemoglobin in the first 28 days of age with a 50% reduction in the need for packed RBC transfusion compared with preterm infants who had delayed cord clamping for 20 seconds. 34 There was no difference between the groups in phlebotomy blood loss. 34 A small pilot study, using a randomized controlled design, in extremely low-birth weight preterm infants (24-32 completed weeks of gestation) showed that delayed cord clamping (30-45 seconds after birth) was safe with no increase in risk of hypothermia, hyperbilirubinemia, and no delay in intubation compared with similar preterm infants who underwent immediate cord clamping.…”
Section: Preterm Infantsmentioning
confidence: 86%
See 1 more Smart Citation
“…33 Rabe and colleagues found that preterm infants born at fewer than 33 completed weeks of gestation and who were randomized to delayed cord clamping for 45 seconds had significantly higher hemoglobin in the first 28 days of age with a 50% reduction in the need for packed RBC transfusion compared with preterm infants who had delayed cord clamping for 20 seconds. 34 There was no difference between the groups in phlebotomy blood loss. 34 A small pilot study, using a randomized controlled design, in extremely low-birth weight preterm infants (24-32 completed weeks of gestation) showed that delayed cord clamping (30-45 seconds after birth) was safe with no increase in risk of hypothermia, hyperbilirubinemia, and no delay in intubation compared with similar preterm infants who underwent immediate cord clamping.…”
Section: Preterm Infantsmentioning
confidence: 86%
“…A randomized controlled trial of late preterm infants (34)(35)(36) weeks' gestation at birth) found that delayed cord clamping, defined as clamping of the umbilical cord 3 minutes after birth, was associated with higher neonatal hemoglobin at birth and at 10 weeks of age compared with infants with early cord clamping (within 30 seconds after birth). 28 There were no differences in the blood glucose levels, polycythemia or need for phototherapy between the groups.…”
Section: Preterm Infantsmentioning
confidence: 99%
“…10 15 It is unclear whether these results can be extrapolated to resource poor countries, where low birth weight babies are predominantly growth retarded. About a third of the preterm infants in the study by Rabe et al 10 were growth retarded and equally distributed between delayed cord clamping and immediate clamping. Necrotising enterocolitis was examined in two trials, and the incidence did not differ between delayed and immediate clamping (111 infants, relative risk 0.76 (0.37 to 1.58)).…”
Section: Summary Pointsmentioning
confidence: 90%
“…6 The haematological effects of delayed cord clamping in preterm infants were studied in four randomised controlled trials from industrialised countries. [7][8][9][10] The observation period lasted four to six weeks and comprised the time the infants were admitted to the neonatal intensive care unit. Many of these infants born before 30 weeks of gestation would not have…”
Section: Is Delayed Cord Clamping Associated With Improved Haematologmentioning
confidence: 99%
See 1 more Smart Citation